2012
DOI: 10.1002/jbm.a.34358
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐hydroxyapatite‐coated PEEK implants: A pilot study in rabbit bone

Abstract: Osseointegration of surface-modified polyetheretherketone (PEEK) implants was studied in vivo. A total of 18 cylinder-shaped PEEK implants were inserted in the femurs of nine New Zealand rabbits; half were coated with nanocrystalline hydroxyapatite (nanoHA) and half were uncoated controls. Healing time was 6 weeks. Samples were retrieved with the implant and surrounding tissue, processed to cut and ground sections, and analyzed histomorphometrically. The implant surfaces were analyzed with optical interferomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 26 publications
4
90
1
1
Order By: Relevance
“…These AM implants likewise demonstrated substantial bone ongrowth and ingrowth to their porous surfaces, with additional bone through growth in the cores. Although similar HA coatings have previously demonstrated a beneficial effect on non-porous titanium surfaces or inert structures, such as PEEK, 26,27 the current study showed that the dip, spin, heat treated nanocrystalline HA coating did not further enhance results compared to uncoated AM implants. The addition of autograft, on the other hand, resulted in significantly increased bone ingrowth and through growth within the AM implant, potentially further promoting osteointegration.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…These AM implants likewise demonstrated substantial bone ongrowth and ingrowth to their porous surfaces, with additional bone through growth in the cores. Although similar HA coatings have previously demonstrated a beneficial effect on non-porous titanium surfaces or inert structures, such as PEEK, 26,27 the current study showed that the dip, spin, heat treated nanocrystalline HA coating did not further enhance results compared to uncoated AM implants. The addition of autograft, on the other hand, resulted in significantly increased bone ingrowth and through growth within the AM implant, potentially further promoting osteointegration.…”
Section: Discussioncontrasting
confidence: 61%
“…For AM+HA implants, a ~20nm layer of HA was applied to implant surfaces using a dip-coating precipitate technique as previously described. 26,27 AM+Auto implants are described in the Animal Model section below. All implants were gamma-sterilized prior to use.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study, using an identical HA coating as in the present study, revealed a higher mean bone-to-implant contact for HA, indicating a higher level of osseointegration. 31 Conversely, due to an unfavorable implant design, a large number of implants were lost due to a lack of primary stability. The design of the implant in the present study has taken into account the result of the previous study in order to achieve better primary stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were large numbers of lost implants due to loss of primary stability since the implants lacked threads. 31 Therefore, the implant was redesigned and now possesses wide and shallow threads for primary stability to allow initial osseointegration. The implant was also designed to be fully submerged into the bone to minimize external loading during healing.…”
mentioning
confidence: 99%
“…Thus, the liquid coating material is evenly spread on the substrate, while excess material is spun down, so that the film thickness can be controlled by speed and process time. This method has been used for coating of PEEK with HA and yielded promising results [46]. (iv) Aerosol-coating is a powder spray method, where the substrate to be coated is exposed to an aerosol containing fine particles of the coating material.…”
Section: Coatingmentioning
confidence: 99%